2004
DOI: 10.1115/1.1860376
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Blade Surface Deterioration by Erosion

Abstract: This paper presents the results of a combined experimental and computational research program to investigate turbine vane and blade material surface deterioration caused by solid particle impacts. Tests are conducted in the erosion wind tunnel for coated and uncoated blade materials at various impact conditions. Surface roughness measurements obtained prior and subsequent to the erosion tests are used to characterize the change in roughness caused by erosion. Numerical simulations for the three-dimensional flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…Surface roughness characteristics were measured after erosion tests in some investigations. 27,29 Surface roughness was found to correlate closely with the erosion rate in terms of variation with the impact angle, velocity, and particle size. The eroded surface roughness did not change beyond a certain limit even with additional mass removal by erosion.…”
Section: Coating and Blade Materials Erosion Studies And Facilitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Surface roughness characteristics were measured after erosion tests in some investigations. 27,29 Surface roughness was found to correlate closely with the erosion rate in terms of variation with the impact angle, velocity, and particle size. The eroded surface roughness did not change beyond a certain limit even with additional mass removal by erosion.…”
Section: Coating and Blade Materials Erosion Studies And Facilitiesmentioning
confidence: 93%
“…The eroded surface roughness did not change beyond a certain limit even with additional mass removal by erosion. 29 Richardson et al 17 also reported that compression system airfoil surface roughness did not change beyond 2000 cycles. Figure 9 (Ref.…”
Section: Coating and Blade Materials Erosion Studies And Facilitiesmentioning
confidence: 96%
“…Hence, he came up with a semi-empirical erosion model, the Finnie model, to predict the erosion numerically. Since then more complex erosion models have been presented, including the Tabakoff model [6], the Tulsa model [7], et al So far one of the most comprehensive models was established by Oka et al [8,9], in which specific conditions involving impact direction, impact velocity, size of particles, and properties of particles and target material were considered. These erosion models have provided the foundation of numerical investigation and wear prediction in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Tabakoff and coworkers [50][51][52] were among the earliest researchers working on numerical prediction of erosion in turbomachinery. Their methods and experiments served as a foundation for other studies in the field.…”
Section: Introductionmentioning
confidence: 99%